Displacement‐Based Seismic Performance Analysis of FRC Frame Structures - Wang, Yingjun; Liang, Xingwen; Du, Shuting (Modelling and Simulation in Engineering, 2025)
In order to improve the seismic performance of RC frame structures, engineering fiber reinforced cementitious composites (FRCs), with properties of tensile strain‐hardening performance and multiple‐crack development, are used in the expected damage parts of reinforced concrete (RC) frame structures to form FRC frame structures. Based on the qualitative description and quantitative indexes of FRC frame structures at different performance levels from the preliminary quasistatic reversed cyclic loading tests of FRC beam‐column assemblies, Perform 3D software was used to complete the static elastoplastic analysis of five‐, eight‐, and 10‐storied FRC frame structures at different performance levels, and their lateral displacement curve patterns were obtained. Furthermore, displacement‐based seismic design of an eight‐storied FRC frame structure under the action of the frequent, basic, and rare intensity was carried out, respectively, and it was also verified by static elastoplastic analysis and dynamic time‐history analysis. The results indicate (1) the bearing capacity of FRC frame structures is 1.48 times that of frame structures, (2) the lateral displacement curve patterns and interstory drift ratio limits of the FRC frame structures at different performance levels proposed are reasonable, and (3) the plastic hinge of the column end in FRC frame structures appears later and slowly, which is conducive to forming a strong column‐weak beam yielding mechanism. The research results can fundamentally improve the earthquake collapse resistance of engineering structures and the application of high‐performance materials in practical engineering, which has extremely important engineering value and academic significance.